Early outcomes from a new regional programme for the surgical management of hypoplastic left heart syndrome. Issue 6 (19th February 2013) - Orr, Yishay; Leclair, Karen; Jacobe, Stephen; Badawi, Nadia; Nicholson, Ian A.; Chard, Richard B.; Sholler, Gary F.; Winlaw, David S.
Abstract Background Early survival and quality of outcome after surgery for hypoplastic left heart syndrome (HLHS) are influenced by patient‐specific factors, the quality of surgery and perioperative care. Some skills are common to the care of other complex neonatal presentations but integrating this expertise is a key challenge for new programmes. We began offering surgery for HLHS from 2006 and provided a regional service from January 2009 and report early outcomes. Methods Prospectively collected data for neonates with HLHS undergoing surgical palliation from January 2006 until June 2011 were analysed. Standard definitions of high‐risk and standard‐risk presentations were utilized. Results Thirty neonates underwent surgical palliation of HLHS with a modified Norwood procedure with an overall survival to stage II palliation of 80%. A total of 46.7% of our patients were categorized as high‐risk, mostly on the basis of low birth weight. Survival to stage II palliation was 100% in standard‐risk patients and 57.1% in the high‐risk group. Conclusion Outcomes for this new programme are comparable to reported outcomes demonstrating the feasibility of integrating a new complex procedure within an existing multidisciplinary unit handling large volumes of other complex neonatal work. Excellent outcomes can be achieved in standard‐risk patients. Outcomes in the high‐risk group may be improved by alternative approaches and rigorous case selection.